Classification of Mouse Retinal Bipolar Cells: Type-Specific Connectivity with Special Reference to Rod-Driven AII Amacrine Pathways - Yoshihiko Tsukamoto; Yoshihiko Tsukamoto; Naoko Omi (Frontiers Media S.A., 2017)
We confirmed the classification of 15 morphological types of mouse bipolar cells by serial section transmission electron microscopy and characterized each type by identifying chemical synapses and gap junctions at axon terminals. Although whether the previous type 5 cells consist of two or three types was uncertain, they are here clustered into three types based on the vertical distribution of axonal ribbons. Next, while two groups of rod bipolar (RB) cells, RB1, and RB2, were previously proposed, we clarify that a half of RB1 cells have the intermediate characteristics, suggesting that these two groups comprise a single RB type. After validation of bipolar cell types, we examined their relationship with amacrine cells then particularly with AII amacrine cells. We found a strong correlation between the number of amacrine cell synaptic contacts and the number of bipolar cell axonal ribbons. Formation of bipolar cell output at each ribbon synapse may be effectively regulated by a few nearby inhibitory inputs of amacrine cells which are chosen from among many amacrine cell types. We also found that almost all types of ON cone bipolar cells frequently have a minor group of midway ribbons along the axon passing through the OFF sublamina as well as a major group of terminal ribbons in the ON sublamina. AII amacrine cells are connected to five of six OFF bipolar cell types via conventional chemical synapses and seven of eight ON (cone) bipolar cell types via electrical synapses (gap junctions). However, the number of synapses is dependent on bipolar cell types. Type 2 cells have 69% of the total number of OFF bipolar chemical synaptic contacts with AII amacrine cells and type 6 cells have 46% of the total area of ON bipolar gap junctions with AII amacrine cells. Both type 2 and 6 cells gain the greatest access to AII amacrine cell signals also share those signals with other types of bipolar cells via networked gap junctions. These findings imply that the most sensitive scotopic signal may be conveyed to the center by ganglion cells that have the most numerous synapses with type 2 and 6 cells.